Ecological Metaphors of Resistance: Mahmoud Darwish’s Poetic Response to Palestinian Occupation - Md. Jobaar Talukder; Md. Maher Ali (ELS Journal on Interdisciplinary Studies in Humanities, 2025)
This article explores Mahmoud Darwish’s use of themes of resistance and nature in his poetry, written during his exile, as a response to the occupation of Palestine. Focusing on specific poems from this period, including “A Diary of a Palestinian Wound,” “A Song to the Northern Wind,” “A Soft Rain in a Distant Autumn,” and “I Love You or I Do Not Love You,” the paper examines how Darwish intertwines the enduring spirit of Palestinian resistance with the natural world. Despite his physical separation from Palestine, Darwish’s poetry consistently reflects a potent sense of resistance and defiance. This study analyzes how Darwish utilizes metaphorical representations of Palestinian landscapes to craft a distinctive narrative of righteous resistance against the colonial oppressors of his homeland, as seen in his selected exile poems. The theoretical framework of this research is anchored in postcolonial and ecocritical literary theories, collectively referred to here as an Eco-resistance approach. Through this lens, the study critically investigates Darwish’s exilic poems, uncovering complex notions of Eco-resistance and offering fresh perspectives on the interrelationship between humans and their land as a form of opposition to colonial aggression. The methodologies applied involve close textual analysis and thematic exploration, contextualized within the historical and cultural backdrop of Darwish’s exile. This research provides broader implications for contemporary understandings of social hierarchies, illustrating how literature can redefine resistance and challenge narratives of colonization by emphasizing the integral connection between people and their environment.